Security and privacy management, techniques, and protocols - Maleh, Yassine 1987 (Advances in information security, privacy, and ethics (AISPE) Book Series,, 2018)
"This book explores theory and practice of information security and privacy. It deals with a wide range of issues, ranging from technical, legal, regulatory, organizational, managerial, cultural, ethical and human aspects of information security and privacy"--